A Comprehensive Review of Blockchain Security: Challenges and Future Prospects - Gopalakrishna, Chandini A (AG Volumes, 2025)
The blockchain is a useful method and service that has shown excellent development and application potential. But there have also been significant security concerns, and a number of attack issues and security flaws in blockchain-based systems have surfaced. Extensive attention has been recently directed towards blockchain security concerns. Review the many studies on the difficulties and potential for blockchain security in this article. This review provides a comprehensive examination of blockchain security, identifying key vulnerabilities such as 51% attacks, smart contract flaws, Sybil attacks, phishing, and insider threats. Real-world case studies and formal verification experiments highlight existing weaknesses and the need for robust defense mechanisms. While blockchain offers inherent advantages for data security, particularly in sectors like healthcare, its limitations hinder widespread adoption. Future advancements will rely on improved technologies, regulatory frameworks, and interdisciplinary applications. Emerging innovations like AI, quantum-resistant cryptography, and interoperability frameworks are poised to play a crucial role in enhancing blockchain resilience and ensuring secure, scalable deployments.